Evaluation of the flexural strength of carbon fiber-, quartz fiber-, and glass fiber-based posts - Ávila Galhano, Graziela [UNESP]; Valandro, Luiz Felipe; Marques de Melo, Renata; Scotti, Roberto; Bottino, Marco Antonio (Wolters Kluwer, 2005)
This study investigated the flexural strength of eight fiber posts (one carbon fiber, one carbon/quartz fiber, one opaque quartz fiber, two translucent quartz fiber, and three glass fiber posts). Eighty fiber posts were used and divided into eight groups (n = 10): G1: C-POST (Bisco); G2: ÆSTHETI-POST (Bisco); G3: ÆSTHETI-PLUS (Bisco); G4: LIGHT-POST (Bisco); G5: D.T. LIGHT-POST (Bisco); G6: PARAPOST WHITE (Coltene); G7: FIBERKOR (Pentron); G8: REFORPOST (Angelus). All of the samples were tested using the three-point bending test. The averages obtained were submitted to the ANOVA and to Tukey's test (p < 0.05). The mean values (MPa) of the groups ÆSTHETI-POST - carbon/ quartz fiber post (Bisco) and ÆSTHETI-PLUS - quartz fiber post (Bisco) were statistically similar and higher than the mean values of the other groups. The mean values of the groups C-POST - carbon fiber post (Bisco), LIGHT-POST - translucent quartz fiber post (Bisco), D.T. LIGHT-POST - double tapered translucent quartz fiber post (Bisco), PARAPOST WHITE - glass fiber post (Coltene) and FIBREKOR - glass fiber post (Pentron) were similar and higher than the group REFORPOST - glass fiber post (Angelus). Copyright © 2005 by the American Association of Endodontists.
Keywords: carbon fiber; glass fiber; silicon dioxide; analysis of variance; materials testing; mechanics; validation process; Analysis of Variance; Carbon; Composite Resins; Dental Materials; Dental Stress Analysis; Elasticity; Glass; Humans; Materials Testing; Microscopy, Electron, Scanning; Pliability; Post and Core Technique; Quartz; Statistics, Nonparametric